Sputter-deposited TiVCrZrW high entropy alloy film: Structure and tribological properties. Issue 24 (15th December 2022) - Ren, Ping; Si, Yanxin; Wang, Ganggang; Wen, Mao; Wang, Weiwei; Yan, Linhui; Yang, Xiaoyang; Song, Qiyao; Li, Zhaohai; Zhang, Shangzhou
Abstract: High-entropy alloy (HEA) films for critical components in aerospace and marine engineering are a class of materials with superior mechanical and tribological properties that can lower material losses and energy costs. Despite recent advances, it is challenging to produce self-lubricating HEA films with low coefficient of friction (CoF) and determine the tribological mechanisms. Herein, TiVCrZrW HEA films were prepared by magnetron sputtering and the structure of all films were optimized via vacuum annealing at different temperatures in the range of 450 °C–900 °C. X-ray diffraction and High-resolution transmission electron microscopy revealed that all the films have a body-centered cubic solid solution structure and that their crystallinity increased with increasing annealing temperature. Tribological tests on a 900 °C annealed film in two-phase (based-oil/film) and three-phase (based-oil/ambient air/film) contact environments revealed a three-phase CoF of ∼0.034 is only about 33% of CoF in a two-phase environment. During the three-phase contact, there was a more pronounced tribochemical reaction that led to the formation of lubricating bimetallic oxides ZrTiO4 and large amounts of V2 O5 that contributed to a lower CoF. Thus, the TiVCrZrW films are capable of self-lubricating by the simple control of contact frictional conditions, presenting a new idea for HEA film tribological application.